OPTIMALISASI JARINGAN INTERNET DENGAN LOAD BALANCING PADA HIGH TRAFFIC NETWORK - Tania Octavriana; Koko Joni; Achmad Fiqhi Ibadillah (JURNAL TEKNIK INFORMATIKA, 2021)
In recent years, the Internet became an important human need in the modern times. In 2019 the number of internet users in Indonesia reached 73.7% of the population as a whole and an increase of 8.9% from the previous year. In State Islamic High School Sidoarjo already provides internet services but existing bandwidth is not distributed evenly between ISP1 and ISP2. In this research, a Load balancing technique is carried out using the Per Connection Classifier (PCC) method. This method divides and classify the data packets to the Gateway connection. QoS Testing was performed using four parameters : Throughput, Jitter, Delay, and Packet Loss are taken the average value by measuring before and after Load balancing. Before Load balancing the uploads and downloads are 19.01 and 19.87 Mbps. From the results of testing the two domain, namely www.google.com and www.youtube.com the Delay was 55 and 39 ms, Jitter was 8 and 17 ms, and Packet Loss was 1% and 19%. Whereas after Load balancing is applied the uploads and downloads are 199.00 and 134.87 Mbps. From the results of testing two domains, the Delay is 21 and 24 ms, both Jitter is 0 ms, and both Packet Loss is 0%.